'Zooming in' on the antecedents of youth sport coaches' autonomy-supportive and controlling interpersonal behaviours: a multimethod study. Issue 2 (April 2021) - Carroll, Mark; Allen, Justine
Grounded in self-determination theory and the motivational model of the coach-athlete relationship, the purpose of this study was to explore the antecedents of youth sport coaches' autonomy-supportive and controlling behaviours using a multimethod approach. Recreational level youth swimming and football coaches (N = 12) participated in semi-structured interviews and were observed leading a coaching session. Interviews were thematically analysed and coaching sessions were analysed using the multidimensional motivational climate observation system. Analysis of the triangulated data revealed that the coaches were both autonomy-supportive and controlling in their interactions with athletes, but predominantly autonomy-supportive. Coaches reported that they coached in this way due to factors associated with their personal orientation (significant others' influence, learning experiences, and beliefs about the role of the coach), the coaching context (time pressure), and perceptions of athletes' characteristics (readiness for autonomy, gender, and quality of motivation). The findings are discussed in relation to personal and social processes that may determine coaching behaviours, and suggestions for coach development and future research are noted.